CONSTRUCTING A COURSE ON INDONESIAN SHADOW PUPPETS FOR INTERNATIONAL STUDENTS - Yosep Bambang Margono Slamet (Soegijapranata Catholic University, 2014)
Abstract: This paper is a course design on Indonesian shadow puppet to promote Indonesian culture to international students as a way of building a cultural bridge to create global citizens. In todays world, it is of paramount importance for every individual from diverse cultural, linguistic, and ethnic backgrounds to understand each other and work together. Creating this course is to introduce and promote an aspect Indonesian culture so that international students are more interested in and knowledgeable of Indonesian people and culture in general. Even though students only learn an aspect of Indonesian culture it is expected that they will be able to explore Indonesian culture in a broad sense.